Experimental study on heating performance of a CO2 heat pump system for an electric bus. (25th May 2021) - Song, Xia; Lu, Daxiong; Lei, Qiang; Cai, Yu; Wang, Dandong; Shi, Junye; Chen, Jiangping
Highlights: A CO2 heat pump system is developed for use in an electric bus. The system delivers good heating performance in cold climate. The effects of operating conditions on system performance are investigated. A fitting formula for the optimum high pressure for the system is given. Abstract: This study investigates the heating performance of a heat pump system for an electric bus by using carbon dioxide (CO2 ) as refrigerant in cold climate. The effects of the outdoor and indoor air temperatures, indoor air flow rate, compressor speed, and the opening step of electronic expansion valve on system performance are examined. The results show that at air temperatures of −20 °C/20 °C (an outdoor temperature of −20 °C and indoor temperature of 20 °C), the system had a heating capacity of 15.3 kW and a coefficient of performance (COP) of 1.78, which shows that the heat pump system for the electric bus can deliver satisfactory heating performance in a cold climate by using CO2 as refrigerant. The heating capacity and COP increased with the indoor air flow rate and decreased as the indoor air temperature increased. Compared with the indoor air flow rate, the optimum high pressure of the system was influenced more by the indoor air temperature. An equation was also derived to relate the temperature of CO2 at the outlet of the gas cooler with the optimum high pressure of the heat pump system for the electric bus, which can be used as the optimum high-pressure control algorithm to maximize the COP.